1997
DOI: 10.1007/s001040050356
|View full text |Cite
|
Sign up to set email alerts
|

Die Wertigkeit der pyloruserhaltenden partiellen Duodenopankreatektomie beim duktalen Pankreascarcinom

Abstract: In a study compiling the data in a prospective manner, the value of the pylorus-preserving duodenopancreatectomy (PPPD) compared to partial duodenopancreatectomy (PD) in patients suffering from ductal pancreatic carcinoma was assessed. Postoperative morbidity, mortality and overall prognosis were analysed. From May 1990 to April 1995 130 patients entered the study; 61 underwent PD, 69 patients had PPPD. The patients were regularly followed up every 6 months and the median follow-up period for all patients was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 14 publications
3
14
0
3
Order By: Relevance
“…The effect of preservation of the pylorus on DGE following pancreatic resection is an ongoing controversy in the surgical literature. Some studies reported a higher incidence of DGE pylorus preservation whereas other authors did not [12, 15, 16, 17, 18, 19, 20, 33, 34, 35]. Consistent with more recent published studies, we did not observe an increased incidence of DGE after preservation of the pylorus [15, 20, 25, 36, 37].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The effect of preservation of the pylorus on DGE following pancreatic resection is an ongoing controversy in the surgical literature. Some studies reported a higher incidence of DGE pylorus preservation whereas other authors did not [12, 15, 16, 17, 18, 19, 20, 33, 34, 35]. Consistent with more recent published studies, we did not observe an increased incidence of DGE after preservation of the pylorus [15, 20, 25, 36, 37].…”
Section: Discussionsupporting
confidence: 81%
“…It has been postulated that the ppWhipple procedure improves postoperative nutritional recovery and therefore benefits quality of life [12, 16, 17, 18, 19, 20, 28]. At our institution, we favor the pylorus-preserving Whipple resection although at present unbiased scientific evidence is lacking to prove the superiority of either type of resection.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…When comparing pylorus-preserving PD and classic Whipple procedure with regard to postoperative morbidity and survival, results from non-randomized studies are highly inconclusive (24)(25)(26)(27)(28)(29)(30). With the growing recognition of evidence-based surgery, randomized controlled trials (RCTs) comparing both procedures emerged, followed by systematic reviews and meta-analyses summarizing the existing literature (31)(32)(33).…”
Section: Postoperative Morbidity Mortality and Survivalmentioning
confidence: 99%